Wind Increases Blinking Behavior in Great-Tailed Grackles (Quiscalus mexicanus) - Yorzinski, Jessica L.; Argubright, Samantha (Frontiers in Ecology and Evolution, 2019)
Animals often adjust their behavior and physiology in response to extreme weather. One reason they do so is because weather can cause sensory impairments but our understanding of this topic is limited. We therefore tested whether wind, a common component of extreme weather, impairs sensory abilities in captive great-tailed grackles (Quiscalus mexicanus). In particular, we examined whether wind influences their blinking behavior, a fundamental aspect of visual processing that limits information intake. We exposed the grackles to simulated wind while recording their blinking behavior. We found that the grackles exhibited higher blink rates and longer blink durations when experiencing windy versus calm conditions. These results indicate that wind influences visual processing in birds and can potentially impair information gathering.